Helminth community structure of 13 species of anurans from Atlantic rainforest remnants, Brazil - Toledo, G. M. [UNESP]; Schwartz, H. O. [UNESP]; Nomura, H. A.Q. [UNESP]; Aguiar, A. [UNESP]; Velota, R. A.M.V. [UNESP]; Da Silva, R. J. [UNESP]; Anjos, L. A. [UNESP] (Cambridge University Press (CUP), 2018)
This study aimed to evaluate the community composition and structure of the helminths found in 13 anuran species, and to evaluate whether this parasite community is determined by anuran characteristics. We found that the helminth fauna of the amphibians from five anuran families consisted of 13 taxa and that Cosmocercidae gen. sp. was the most prevalent taxon, followed by Oswaldocruzia subauricularis. Host body size was a determining factor of the composition and structure of the parasitic fauna. Helminth abundance and richness were positively correlated with host body size. The host Leptodactylus latrans had the highest helminth richness (n = 8). The frog Hypsiboas faber had the greatest helminth diversity (H′ = 0.711). The mean helminth species richness and diversity differed significantly between host species (P < 0.05). Taken together, our data indicate that, in sympatric species of amphibians, the morphological and behavioural characteristics of the hosts are important for structuring the helminth parasite communities.